Pengaruh Jenis Pelarut Dan Waktu Ekstraksi Terhadap Sitronelol Anti Nyamuk Dari Ekstrak Geranium Radula Cavan (Daun Ambre) - Anissa, Syavrielya; Adira Nanthalia; Retno Dewati (Jurnal Serambi Engineering, 2025)
Geranium Radula Cavan, also known as Ambre leaf, is a mosquito-repellent plant that grows in the regions of Sumatra and Central Java. This plant can be used as a natural mosquito repellent to protect humans from mosquito disturbances or bites by applying or spraying it onto the body or clothing. The essential oil extracted from Ambre leaves contains major compounds such as citronellol (C₁₀H₂₀O) and geraniol (C₁₀H₁₈O). These compounds produce a distinctive aroma that mosquitoes find unpleasant. This study aims to determine the effect of solvent type (96% Ethanol; Ethyl Acetate; Chloroform; N-Hexane; and Benzene) and extraction duration (1 day; 2 days; 3 days; 4 days; and 5 days) on citronellol content and essential oil yield, in order to identify the most optimal process conditions. The highest citronellol content and essential oil yield were obtained at 28,22% and 19,63%, respectively, using 96% ethanol as the solvent with a 4-day soaking duration. GC-MS analysis was used to determine the citronellol content in the essential oil, which had been extracted and purified through distillation. The solvent-to-leaf ratio used in the extraction process was 10:1 mL/g.